2004
DOI: 10.1021/ol036184e
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Cross-Coupling of Stereospecific Potassium Cyclopropyl Trifluoroborates with Aryl Bromides

Abstract: [reaction: see text] Stereospecific cyclopropanation of alkenylboronic esters of pinacol followed by in situ treatment with excess KHF(2) afforded the corresponding potassium cyclopropyl trifluoroborates in high yields, which then underwent Suzuki-Miyaura cross-coupling reactions with aryl bromides to give cyclopropyl-substituted arenes in good yields with retention of configuration. This promises to be a useful method for the synthesis of enantiomerically pure cyclopropanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 52 publications
1
36
0
1
Order By: Relevance
“…Indeed, palladiumcatalyzed reaction of alkenylborane esters of pinacol with CH 2 N 2 , according to the Vaultier protocol, 70 followed by in situ treatment with KHF 2 afforded stereo-defined potassium cyclopropyltrifluoroborates in good to excellent yields (Scheme 24). 71 As expected, trans-and cis-cyclopropyltrifluoroborates were generated from (E)-and (Z)-alkenylboronic esters, respectively. 70 Preparation of highly functionalized 1,2,3-substituted potassium cyclopropyltrifluoroborates has been accomplished from allylic alcohols.…”
Section: Potassium Organotrifluoroborates Via Transmetalation Reactionssupporting
confidence: 61%
See 1 more Smart Citation
“…Indeed, palladiumcatalyzed reaction of alkenylborane esters of pinacol with CH 2 N 2 , according to the Vaultier protocol, 70 followed by in situ treatment with KHF 2 afforded stereo-defined potassium cyclopropyltrifluoroborates in good to excellent yields (Scheme 24). 71 As expected, trans-and cis-cyclopropyltrifluoroborates were generated from (E)-and (Z)-alkenylboronic esters, respectively. 70 Preparation of highly functionalized 1,2,3-substituted potassium cyclopropyltrifluoroborates has been accomplished from allylic alcohols.…”
Section: Potassium Organotrifluoroborates Via Transmetalation Reactionssupporting
confidence: 61%
“…Other palladium catalysts could be used in this coupling, such as PdCl 2 (dppf) and Pd(OAc) 2 in conjunction with 2-biphenyldicyclohexylphosphane. 71 The latter was also chosen for the coupling of 1,2,3-trisubstituted cyclopropyltrifluoroborates (Scheme 106). 72 In that case, some competitive reduction of the trifluoroborate moiety was also observed.…”
Section: Coupling With Potassium Alkyltrifluoroboratesmentioning
confidence: 99%
“…Initial work by the groups of Marsden, [12] Charette, [13,14] Deng, [15][16][17][18][19][20][21][22] and Soderquist [23] revealed that geometrically pure (racemic) cyclopropylborons could be coupled under palladium(0) catalysis with a broad array of activated coupling partners in good yields and complete retention of configuration (Table 1). Both boronic esters (entries 1-3), boronic acids (entries 4-8), potassium trifluoroborate salts (entry 9), and boranes (entry 10) could be used with sp 2 -based and activated sp 3 -based electrophiles.…”
Section: Couplings Of Cyclopropyl Boronic Estersmentioning
confidence: 99%
“…For example, Deng reported in 2004 the synthesis of racemic substituted arylcyclopropanes via the Suzuki coupling of potassium cyclopropyl trifluoroborates. 85 The cyclopropylboron reagents 106 utilized in this study were prepared in two steps from the corresponding alkenylboronic acids 105 through formation of the pinacolboronic ester followed by cyclopropanation with diazomethane in the presence of palladium acetate (Scheme 36). The reaction proceeded stereospecifically, allowing the transposition of the geometry of the alkene to the cyclopropane.…”
Section: C) Suzuki Reaction Of Cyclopropylboronic Acids and Cyclopropmentioning
confidence: 99%